UMA PROPOSTA DE MODELO CONCEITUAL DE DESDOBRAMENTO DE PROCESSOS E DE GOVERNANÇA DE INDICADORES: UM ESTUDO DE CASO EM UMA ÁREA DE UMA EMPRESA INTEGRADA DE ENERGIA - Warrak, Aziz Khazzah El (2012)
This study aims to develop a governance structure within an organization that enables to evaluate its performance in various levels through indicators identified in the processes deployment from level 1 to levels 2 and 3. For that, it was necessary to study concepts related to performance measurement, business process management, value chain, processes mapping and deployment, architecture and governance processes, process measurement and process manager. The methodology considers an applied research, a qualitative approach, exploratory character, taking, as research methods, a case study and an extensive literature revision. Data were collected through documents, interviews and participant observation and analyzed by the methods of construction of explanation and qualitative content analysis. The results obtained in this work were a conceptual model that allows the deployment of processes and evaluation of their performance at various levels, as well as the perception of respondents about the model and over its implementation in the case study.